Utility and safety of adenosine challenge for subtle ventricular pre‐excitation in the pediatric population. (22nd April 2019) - Follansbee, Christopher W.; Beerman, Lee B.; Wu, Liwen; Bertolet, Marnie; Arora, Gaurav
Abstract: Introduction: Adenosine challenge (AC) can be used to evaluate possible Wolff‐Parkinson‐White (WPW) pattern on an electrocardiogram (ECG). Despite the use of this technique, there is a paucity of studies in the pediatric population evaluating the efficacy, safety, and outcomes of this testing modality. Methods and Results: All ACs performed from January 2009 to June 2017 were retrospectively reviewed. Patient demographics, adenosine dosing, results, adverse effects, and outcomes including results of electrophysiology studies (EPS) were reviewed. Analysis was conducted between AC positive and negative cohorts. ECG criteria of shortest PR interval, longest QRS duration, and the number of suspected pre‐excited leads were evaluated for inter‐rater reliability and correlation to positive AC. Fifty‐six AC (n = 51) were performed (median age, 13.8; range, 0.3‐20 years). Forty‐one AC were pre‐EPS and 15 post‐EPS due to concern for recurrent WPW. Thirty‐one (76%) pre‐EPS AC were negative, 9 (22%) positive, and 1 (2%) equivocal. EPS was performed following seven positive AC revealing 5 (71%) left posterior and 2 (29%) right posteroseptal AP. The 15 post‐EPS AC were all found to be negative. Mean effective adenosine dose was 0.2 ± 0.11 mg/kg. No adverse events were reported. Mean follow up duration after AC was 314 ± 482 days with no documented arrhythmias. Conclusion: Adenosine challenge is an effective and safe testing modality for subtle WPW in the pediatric population. In our population, there were no adverse events or documented arrhythmias in patients following a negative study.